Chemical composition, antibacterial activity of essential oil Citrus sinensis l. (Sweet orange)and formulation of a pharmaceutical form - Juárez, José R. (2010)
This study aimed to characterize the chemical components of essential oil of Citrus sinensis L., determine its antibacterial activity and make dosageforms, mainly for local use. The essential oil was obtained from the dried leaves of the selected species, using a hydrodistillation system with water steam sweep; tests were conducted miscibility and determination of physical constants, such as specific gravity, refractive index and optical rotation. The chemical composition was determined by Gas Chromatography/Mass Spectrometry (CG/EM), standing out in the sugiero: chromatogram spectral signals in the elucidating: Limonene, beta-linalool, decanal and 2 (10)-pinene(1S,5S)-(-)-. The determination of antibacterial activity in vitro was tested by agar diffusion method and the formation of inhibition halos against strains of Gram (+), as Staphylococcus aureus ATCC 25,933 and Staphylococcus epidermidis, demonstrating significant antibacterial activity at concentrations 100 and 50% respectively, but not with Gram (-): Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa ATCC 27853. These results gave us the guidance to design dosage forms for local use, formulated: a carbomer based gel, a lotion based in ethanol and isopropyl alcohol and mouthwash. The results of the stability studies of the formulations, as well as tolerance and irritability with human tissue of the products show favorable results for use in skin diseases like acne, and in the case of mouthwash as a good oral antiseptic. The study has revealed that the essential oil of Citrus sinensis L. has antibacterial activity against strains of Staphylococcus aureus ATCC 25,933 and Staphylococcus epidermidis, also allow the preparation of pharmaceutical forms for local use.